Circulating matrix metalloproteinases in children with diabetic ketoacidosis. Issue 2 (4th February 2016) - Garro, Aris; Chodobski, Adam; Szmydynger‐Chodobska, Joanna; Shan, Rongzi; Bialo, Shara R; Bennett, Jonathan; Quayle, Kimberly; Rewers, Arleta; Schunk, Jeffrey E.; Casper, T. Charles; Kuppermann, Nathan; Glaser, Nicole; et al.
Abstract : Background and objective: Matrix metalloproteinases (MMPs) mediate blood–brain barrier dysfunction in inflammatory disease states. Our objective was to compare circulating MMPs in children with diabetic ketoacidosis (DKA) to children with type 1 diabetes mellitus without DKA. Research design and methods: This was a prospective study performed at five tertiary‐care pediatric hospitals. We measured plasma MMP‐2, MMP‐3, and MMP‐9 early during DKA (time 1; within 2 h of beginning intravenous fluids) and during therapy (time 2; median 8 h; range: 4–16 h). The primary outcome was MMP levels in 34 children with DKA vs. 23 children with type 1 diabetes without DKA. Secondary outcomes included correlations between MMPs and measures of DKA severity. Results: In children with DKA compared with diabetes controls, circulating MMP‐2 levels were lower (mean 77 vs. 244 ng/mL, p < 0.001), MMP‐3 levels were similar (mean 5 vs. 4 ng/mL, p = 0.57), and MMP‐9 levels were higher (mean 67 vs. 25 ng/mL, p = 0.002) early in DKA treatment. MMP‐2 levels were correlated with pH at time 1 (r = 0.45, p = 0.018) and time 2 (r = 0.47, p = 0.015) and with initial serum bicarbonate at time 2 (r = 0.5, p = 0.008). MMP‐9 levels correlated with hemoglobin A1c in DKA and diabetes controls, but remained significantly elevated in DKA after controlling for hemoglobin A1c (β = −31.3, p = 0.04). Conclusions: Circulating MMP‐2 levels are lower and MMP‐9 levels are higher in children during DKA compared with levels in children with diabetes without DKA. Alterations in MMP expression could mediate BBB dysfunction occurring during DKA.